2022
DOI: 10.3390/pathogens11101107
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Aujeszky’s Disease in Wild Boar from Southeastern France

Abstract: Aujeszky’s disease virus (ADV), also known as pseudorabies virus, causes an important neurological infection with a major economic and health impact on animal husbandry. Here, we serologically screened muscle fluid from wild boar (Sus scrofa) for the presence of anti-ADV antibodies. Animals were caught during two hunting seasons (2019–2020 and 2021–2022) from three areas in southeastern France known to be endemic with wild boar populations. A total of 30.33% of the 399 tested animals scored positive for anti-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Apparently, spillovers between wild boars and pigs are not a frequent occurrence [97,98]. In this study, we observed a seroprevalence of 29.4%, showing a strong synergy with what was found in the European panorama [99][100][101]. However, AD viral circulation necessitates systematic checks to prevent possible impairment of the eradication plan in the regional territory.…”
Section: Discussionmentioning
confidence: 50%
“…Apparently, spillovers between wild boars and pigs are not a frequent occurrence [97,98]. In this study, we observed a seroprevalence of 29.4%, showing a strong synergy with what was found in the European panorama [99][100][101]. However, AD viral circulation necessitates systematic checks to prevent possible impairment of the eradication plan in the regional territory.…”
Section: Discussionmentioning
confidence: 50%
“…CFT is the least used due to its lower sensitivity concerning other indirect methods [ 28 ]. Serological surveys are widely applied to study the presence and distribution of infectious diseases in wild animals [ 29 ]. ELISA is the most widely chosen method for epidemiological studies in wildlife populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, they tested negative for WNV and the influenza A virus [ 7 ]. We conducted a seroepidemiological survey for Aujeszky’s disease virus in 399 wild boars from southeastern France, revealing a high prevalence of 30% [ 8 ].…”
mentioning
confidence: 99%